2014
DOI: 10.1063/1.4897624
|View full text |Cite
|
Sign up to set email alerts
|

Increased piezoelectric energy harvesting from human footstep motion by using an amplification mechanism

Abstract: In this paper, we propose a piezoelectric energy harvester to scavenge the impact energy from human footsteps at low input frequencies. The device consists of an amplification mechanism and piezoelectric bimorphs. When a human foot strikes the proposed harvester, the amplification mechanism deforms the piezoelectric bimorphs in the 31-mode to produce a large mechanical strain, meaning that the output power can be generated with high efficiency. A maximum output power of 27.5 mW was generated by the proposed ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…In order to improve the output power of such insole harvesters, amplification mechanisms were proposed to increase the effective strain in the piezoelectric material, as shown in Figure 3 [16]. With novel amplification mechanisms, the effective strain can be greatly improved, and the output electric power is much more than the harvester of traditional constructions [30]. It is reported that the magnetic rotary generator can produce approximately two orders of magnitude more power than either of the piezoelectric systems [14][15][16].…”
Section: Human Walking Induced Energy Conversionmentioning
confidence: 99%
“…In order to improve the output power of such insole harvesters, amplification mechanisms were proposed to increase the effective strain in the piezoelectric material, as shown in Figure 3 [16]. With novel amplification mechanisms, the effective strain can be greatly improved, and the output electric power is much more than the harvester of traditional constructions [30]. It is reported that the magnetic rotary generator can produce approximately two orders of magnitude more power than either of the piezoelectric systems [14][15][16].…”
Section: Human Walking Induced Energy Conversionmentioning
confidence: 99%
“…Howells investigated a mechanism with lead screw and cam that activated piezoelectric cantilevers, while Alghisi explored the activation of piezoelectric membranes with a metal ball that was free to move in a cavity . Xie designed a device that used an amplification mechanism with sliders to generate high strain in piezoelectric bimorphs . Studies on nonlinear techniques for piezoelectric energy harvesting from human motion have previously been proposed by Green and Cao …”
Section: Introductionmentioning
confidence: 99%
“…[5] Xie designed a devicet hat used an amplificationm echanism with sliders to generateh igh strain in piezoelectric bimorphs. [6] Studies on nonlinear techniques for piezoelectrice nergy harvesting from human motionh ave previously been proposed by Green [7] and Cao. [8] Investigations on energy-harvesting floors have been conductedb yr esearchers from academia and companies.S harpes designed atile based on PZT cymbal transducers capable of powering wireless signal transmissions, [9] and Bischur proposed using PVDF-based modules.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PGs have attracted extensive research effort during the last decade. [3][4][5] Given the capacitive nature of PGs, their energy harvesting capability can be increased by several hundred percent by connecting themselves to some power conditioning circuits, such as the synchronized switch harvesting on inductor (SSHI) 6 and other synchronized switch interface circuits. 7 In SSHI, the power conditioning circuit detects the maximum deforming instants of a PG, and simultaneously forms an inductive shortcut for the charge stored in the PG, such that the voltage across the piezoelectric element can be inverted after half of an RLC cycle.…”
mentioning
confidence: 99%